Stereodivergent assembly of tetrahydro-γ-carbolines via synergistic catalytic asymmetric cascade reaction - Shi-Ming Xu (Nature Portfolio, 2019)
Tetrahydro-γ-carbolines are the basic structural unit in many natural products and pharmaceuticals. Here, the authors report a synergistic Cu/Ir system to assemble chiral tetrahydro-γ-carbolines via a stereodivergent allylation followed by a stereoselective iso-Pictet-Spengler cyclization.